Own the room : business presentations that persuade, engage & get results - Booth, David (McGraw-Hill, 2010)
Imagine if every presentation received rapt attention and buy-in from the audience. Start getting these results with Own the Room, featuring the renowned Eloqui Method-innovative techniques that leave boring behind. Own the Room will give you a communication toolkit to make any presentation lively, compelling, and memorable.